PROTOCOL: INTERVENTIONS FOR PROMOTING AND OPTIMIZING BREASTFEEDING PRACTICES: AN OVERVIEW OF SYSTEMATIC REVIEW - Khatib, Mahalaqua Nazli; Fulzele, Punit; Ahmed , Mahajeeb; Chaudhary, Sonali; Saxena, Deepak; Bharadwaj, Pankaj; B, Unnikrishnan; Gaidhane, Abhay M; Zahiruddin, Dr Quazi Syed (International Journal of Psychosocial Rehabilitation, 2020)
Optimal breastfeeding practices are vital for child survival, growth, and development. The purpose of this overview is to evaluate the effectiveness of different interventions for promoting and optimizing breastfeeding. We will include systematic reviews (including trials from Low-Income and Low Middle-Income countries) that have evaluated the effect of various interventions for promoting and optimising breastfeeding. We will search various electronic databases. We will follow the standard methodology as suggested by Cochrane handbook for Systematic Reviews of Interventions. Two sets of reviewers will undertake screening followed by data extraction and assessment of methodological quality of included SRs. We will present the evidence in texts and tables by each of our pre-specified outcomes. We will mainly focus on summarizing and thematically categorizing the intervention and its effectiveness. Our discussion will focus where we have found high quality evidence of important effects. Finally, we will make recommendations for future systematic reviews and clinical research. We intend to look into the evidence generated in LICs and LMICs and hence generalizability of the findings will be restricted to LICs and LMICs.